The Positioning of Universities in Collaborative Models as Clusters in a Knowledge Based Economy - Adrian D. Tanţău; Nicolae Al. Pop; Daniela Hîncu; Laurenţiu Frăţilă (Amfiteatru Economic Journal, 2011)
The most significant research about knowledge based economy is concentrated on innovation. Research about entrepreneurial thinking at the university level and positioning of universities in collaborative models as clusters are in the early stages. The new approach that we propose in this research is positioning the university as a main promoter and integrator of organizations in clusters and innovations enterprises networks in a global network of knowledge. The results of this research are based on data that was obtained through questionnaires from organizations that are active in the ITC industry in the region of Bucharest-Ilfov. These characteristics are representative for different types of clusters.
Keywords: I23; L26; P13; O32; 330; economic cluster; institutional cluster; objectives for cluster establishing; specialized knowledge